1998
DOI: 10.1021/jp980340v
|View full text |Cite
|
Sign up to set email alerts
|

Second Virial Coefficient of Arborescent Polystyrenes and Its Temperature Dependence

Abstract: The solution behavior of arborescent (highly branched) polymers was examined in terms of A 2 variation with polymer structure, solvent type, and temperature. Two series of graft polymers in three successive generations were examined, with side chains of either 5000 (S05 series) or 30 000 (S30 series). Scaling relationships A 2 ∝ M w a were found for both series, with a = −0.94 or −0.97, consistent with rigid-sphere behavior. Temperature-dependent measurements were carried out in cyclohexane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…As the generation number increases there is a significant decrease in A 2 : This decrease is probably largely due to chain architecture but also could be due to the decreased P2VP content (from 90 to 81%). The role have chain architecture is important because this same decrease in A 2 has been seen in arborescent polystyrene homopolymers [1,24]. The high level of branching leads to the molecules having a much smaller average dimension and higher segment density when compared with a linear polymer of the same molecular weight.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…As the generation number increases there is a significant decrease in A 2 : This decrease is probably largely due to chain architecture but also could be due to the decreased P2VP content (from 90 to 81%). The role have chain architecture is important because this same decrease in A 2 has been seen in arborescent polystyrene homopolymers [1,24]. The high level of branching leads to the molecules having a much smaller average dimension and higher segment density when compared with a linear polymer of the same molecular weight.…”
Section: Resultsmentioning
confidence: 85%
“…The high level of branching leads to the molecules having a much smaller average dimension and higher segment density when compared with a linear polymer of the same molecular weight. Studies in the literature have shown a decrease in A 2 with polymer molecular weight for branched polymers compared to equivalent molecular weight linear molecules [26,27] and according to Gauthier et al A 2 for arborescent homopolymer polystyrene in solution is more strongly influenced by branching functionality than by the overall molecular weight of the polymer [24]. Gauthier et al observed that A 2 became close to zero in a good solvent as the branching functionality of arborescent polystyrenes increased which agrees with the results observed in this study [1,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simplified representation of the generation‐based synthesis of arborescent polymers is provided in Scheme . Further progress was made by Gauthier et al to gain better understanding of the morphology and solution properties of arborescent polymers using light scattering, atomic force microscopy, fluorescence spectroscopy, and small‐angle neutron scattering …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Comparatively many basic studies concern the behavior of star shaped polymers as compared with their linear analogs. [10,12,[17][18][19][20][21][22][23][24][25] Here it is interesting to note that the application of the blob theory predicts a decrease in the solubility of a nonlinear polymer as compared to the corresponding linear polymer. [26] Despite the abundant literature (the above compilation is far from being complete) a comparison of the Flory-Huggins interaction parameters for a linear and a branched polymer homolog with a given, thermodynamically favorable solvent is still missing to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%